2021
DOI: 10.1038/s41419-021-03445-w
|View full text |Cite
|
Sign up to set email alerts
|

Sensing soluble uric acid by Naip1-Nlrp3 platform

Abstract: Uric acid (UA), a product of purine nucleotide degradation able to initiate an immune response, represents a breakpoint in the evolutionary history of humans, when uricase, the enzyme required for UA cleavage, was lost. Despite being inert in human cells, UA in its soluble form (sUA) can increase the level of interleukin-1β (IL-1β) in murine macrophages. We, therefore, hypothesized that the recognition of sUA is achieved by the Naip1-Nlrp3 inflammasome platform. Through structural modelling predictions and tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 77 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…However, all in vivo studies are based on low serum UA levels of 2–5 mg/dL that are not considered as HU in humans. In vitro studies using crystalline UA (cUA) consistently report pro-inflammatory and cytotoxic effects in murine and human monocytes and macrophages [ 17 , 18 , 19 , 20 , 21 ], similar to what has been broadly reported with other crystalline particles [ 22 , 23 , 24 ]. While these effects likely attribute to UA microcrystal contaminations, recent evidence indicates that microcrystal-free soluble UA (sUA) preparations rather attenuate pro-inflammatory effects of human monocytes [ 25 ].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, all in vivo studies are based on low serum UA levels of 2–5 mg/dL that are not considered as HU in humans. In vitro studies using crystalline UA (cUA) consistently report pro-inflammatory and cytotoxic effects in murine and human monocytes and macrophages [ 17 , 18 , 19 , 20 , 21 ], similar to what has been broadly reported with other crystalline particles [ 22 , 23 , 24 ]. While these effects likely attribute to UA microcrystal contaminations, recent evidence indicates that microcrystal-free soluble UA (sUA) preparations rather attenuate pro-inflammatory effects of human monocytes [ 25 ].…”
Section: Introductionmentioning
confidence: 65%
“…Several in vitro studies reported that UA triggers the release of pro-inflammatory mediators, including NLRP3 inflammasome-mediated IL-1β production in lipopolysaccharide (LPS) and monosodium urate (MSU) crystal-stimulated murine and human monocytes and macrophages [ 17 , 18 , 19 , 20 , 21 ]. However, such studies prepared UA by pre-warming UA powder at 37 °C in culture medium, a preparation method that does not fully solubilize UA so that UA microcrystals remain as contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…Although HUA is considered to be an adverse factor in cardiovascular events, the general treatment of asymptomatic HUA to reduce cardiovascular risk is not recommended. 33 This study is the first to assess the mediating effects of chronic inflammation in PBMCs on the association between high SUA levels and coronary calcium deposition. Chronic inflammation is recognized as the major underlying cause of many pathologies including cardiovascular and cerebrovascular events, with mononuclear cells and cytokines playing a critical role in the initial stages of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear how intracellular uric acid is recognized and activates signaling pathways. Recently, NAIP1 was reported to directly recognize intracellular uric acid and induce the activation of NLRP3 in mice [104]. However, the binding of uric acid with human NAIP1 is weak [104], so the effect of uric acid may be caused by other molecules in humans.…”
Section: Inflammasomementioning
confidence: 99%